Book Review: The Politics of Language Contact in the Himalaya - Poudel, Tikaram (Journal of Education and Research, 2020)
The arguments of The Politics of Language Contact in the Himalaya are grounded in the multidisciplinary nature of area studies i.e., linguistics, political science, anthropology and geography. Focusing on the area study of the trans-border region of the Himalaya, the contributors enrich their arguments through specific case studies of their respective areas. For all the contributors, the issues of language contact are central and all of them provide contextual analyses of this issue. The contributors raise placing their issues in the emerging discourse of language contact making the collection accessible not only to linguists but also to scholars interested in anthropology, sociolinguistics, political science and Asian studies.